Pengaruh Wabah Virus Corona Terhadap Return Saham Perusahaan Manufaktur di Bursa Efek Indonesia (Event Study Pada Sub Sektor Mesin dan Alat Berat) - Putu Trisna Eka Yanti (Universitas Pendidikan Ganesha, 2022)
Abstrak Economic growth in the country, the stock market has an important role in growing the industry in the era of globalization. The emergence of share prices that can be found in the capital market, so from this it is said that a company is capable of being used as a measurement tool to find the conditions described in the company's financial performance, so that it can be expressed in a reasonable state and under normal conditions, the more Financial performance is well exposed to a company, then of course it will impact on its share price which will show better conditions or increase growth and from this, of course, beneficial returns for investors will also experience increased growth as well. Stock exchanges in a country are generally sensitive to events in their surroundings, including non-natural events that have occurred to date, namely the presence of the corona virus. Researchers carried out this research because it has the aim to find out how the impact or influence of the emergence of the corona virus outbreak which affects the stock returns of manufacturing companies on the Indonesia Stock Exchange and this can be seen from the inequality of the average abnormal stock returns presented previously and presented after. there is news about the outbreak of the corona virus in Indonesia. Researchers use this type of event study research supported by secondary data obtained indirectly because of the media as an intermediary. The population used by researchers is all companies engaged in manufacturing that have been registered on the IDX. Then the researcher used the method or sample collection technique with the purposive judgment sampling method. The results of this study show firstly, due to the wide spread caused a decrease in consumer demand for goods produced and the information about Covid-19, the production of heavy equipment was slightly disrupted due to components imported from China being delayed in February. So that there is the effect of the corona virus outbreak on stock returns as seen from the inequality of the average abnormal return that has occurred before and after the news of the outbreak of the corona virus in Indonesia. Second, it shows that the market shows results that lead to negative information on the announcement of the corona virus outbreak in Indonesia, which is marked by a decrease in the average abnormal return that has occurred in the period that has been observed. So it can be seen that the information received is in a sufficiently strong condition so that it can have an impact on market reactions. Keywords: Plague, Return, Stock